Strengthening State Security Function for the State Sovereignty in Immigration Perspective (Strengthening State's Security of Immigration Function for the State Sovereignty) - Asyam N. A, Farid (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The correlation between State Security is inseparable from the state sovereignty. In its implementation, State Security is achieved through law enforcement by agencies which become state instruments according to their respective duties and tasks. State Security is part of the fourth Immigration function which has the aim of protecting State Sovereignty from foreign threats in the perspective of Immigration. The Crime Act, which at present is no longer in a small scope, it’s already a matter that cannot be limited by a national boundary, or known as Transnational Organized Crime. There are a lot of crimes threatening State Security that have arisen due to threats from abroad. Therefore, the formulation of the problem examined in this paper is what the threats are to state security in the perspective of Immigration for state sovereignty. The research method used is normative legal research that is qualitative in nature and mixed thinking logic (deductive and inductive). From the results of the study, it can be seen that the Immigration problem has a direct impact on State Security. So that the need for seriousness in strengthening Immigration in the function of state security for national sovereignty. The Directorate General of Immigration must be the foremost authority in State Security in order to safeguard State Sovereignty with a philosophical guardian of the nation's authoritative gate (bhumi pura wira wibawa).